A randomized placebo-controlled trial of rush preseasonal depigmented polymerized grass pollen immunotherapy* - Pfaar, Oliver; Klimek, Ludger (Allergy, 2012)
Abstract: Background: Specific subcutaneous immunotherapy (SCIT) for seasonal rhinoconjunctivitis with unmodified allergen extracts is effective, but limited by risk of side-effects and involves treatment over 3 years. We examined a depigmented polymerized grass pollen extract for immunogenicity and for clinical efficacy in a rush preseasonal regimen. Methods: Depigmented polymerized grass pollen extract was tested for proliferation and cytokine production by peripheral blood mononuclear cells. A prospective, double-blind, placebo-controlled trial of 195 grass pollen allergic patients treated with preseasonal rush immunotherapy using depigmented polymerized allergenic extract of mixed grass pollen was performed over 2 years. Primary outcome was combined symptom and medication score (SMS) during the peak of the second grass pollen season. Secondary outcomes included combined score over the whole season, during the first grass pollen season, individual symptom and medication scores, quality of life, well days/hell days and responder analysis. Adverse events were classified using the EAACI scale. Grass pollen-specific IgE and IgG4 were measured before and during treatment. Results: Depigmented polymerized extract stimulated dose-dependent T-cell proliferation and cytokine production. Patients treated with preseasonal SCIT showed improved combined scores during peak season at year 2 (median 3.93, interquartile range 0.77-6.27 vs median 5.86 for placebo, 3.11-8.36, P < 0.01). Most secondary outcomes were significantly better for active treatment. Side-effects were minimal, with no grade 3 or 4 reactions. Conclusions: Depigmented polymerized grass pollen extract is immunogenic and clinically effective in rush preseasonal SCIT. This form of immunotherapy may be an attractive option for some patients.